Efeitos do ciclamato de sódio no rim fetal de ratos: estudo morfométrico - Arruda, José Germano Ferraz de (2004)
The cyclamate is used as artificial non-caloric sweetner in a wide variety of foods and beverages, being 30 times as sweet as sugar without the bitter after-taste of saccharin. It appears in the composition of the products as sodium and calcium cyclamates and cyclamic acid. The purpose of this research was to assess the effect of sodium cyclamate in kidneys of rats fetuses considering morphometric changes of glomerulus, proximal and distal convoluted tubules, and collecting duct. Ten pregnant rat (Rattus norvegicus) weighting an average of 238 g were divided into two groups: 5 in the control group and 5 in treated group with sodium cyclamate. Between the 10th and the 14th pregnancy day, 5 rats received an intraperitoneal daily injection of 60 mg/kg of body weight of sodium cyclamate during 5 days. At the 20th, the animals were sacrificed and the fetuses were fixed in Alfac solution, included in paraffin, sectioned and stained with haematoxyline and eosine. Morphometry by the karyometric technique was the method used. The results showed that the use of sodium cyclamate was effective in the reduction of fetal and placentae weight, and lenght of umbilical cords. There was a significant increase in glomerular volume and in cell nuclei size of proximal and distal convoluted tubules and collecting duct, suggesting nephrotoxicity.